Changing rapid weather variability increases influenza epidemic risk in a warming climate. (13th March 2020) - Liu, Qi; Tan, Zhe-Min; Sun, Jie; Hou, Yayi; Fu, Congbin; Wu, Zhaohua
Abstract: It is believed that the continuing change in the Earth's climate will affect the viral activity and transmission of influenza over the coming decades. However, a consensus of the severity of the risk of an influenza epidemic in a warming climate has not been reached. It was previously reported that the warmer winter can reduce influenza epidemic caused mortality, but this relation cannot explain the deadly influenza epidemic in many countries over northern mid-latitudes in the winter of 2017–2018, one of the warmest winters in recent decades. Here, we reveal that the widely spread 2017–2018 influenza epidemic can be attributed to the abnormally strong rapid weather variability. We demonstrate, from historical data, that the large rapid weather variability in autumn can precondition the deadly influenza epidemic in the subsequent months in highly populated northern mid-latitudes; and the influenza epidemic season of 2017–2018 was a typical case. We further show that climate model projections reach a consensus that the rapid weather variability in autumn will continue to strengthen in some regions of northern mid-latitudes in a warming climate, implying that the risk of an influenza epidemic may increase 20% to 50% in some highly populated regions in the later 21st century.